Factors predicting Malaysian university students' online shopping attitude and intentions - Jadehkenari, Marzieh Zendehdel (2013)
Internet has changed the ways business is conducted and the ways producers and consumers interact. Internet is a business medium that allows the firms to generate interactive online environments that permit consumers to gather and assess information, evaluate purchase intention and directly purchase products at their own convenience. The Malaysian government has made a tremendous effort in equipping its society with electronic environment, particularly on internet commerce and for Emarketers. Paying attention to the factor that affects the attitude towards online shopping intention is essential for the marketers to develop their marketing strategies to increase sales. Attitude towards online shopping is a significant predictor for making online purchases. In addition intention is an important determinant of online shopping behavior and can be counted as the best estimate of future behavior to market researcher. Based on the developments of the Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB) and diffusion of innovation theory (DOI) which holds an e-business perspective, it can be understood that these theories are capable of providing a valid basis for explaining and predicting consumers‟ attitudes that lead to intention towards online shopping. This study examines the factors predicting students‟ online shopping attitude and intention at universities of Klang Valley area in Malaysia. In this study, cluster sampling method was used. Firstly, the whole population was divided into different cluster (public and private). Then, a number of universities from each selected clusters through simple random sampling was chosen, four public and four private universities were randomly selected. Hence students who enrolled in each faculty and institute were chosen. Among 400 questionnaires that were distributed, about 380 were returned, but only 375 have complete answers. Present study has shown collectivism/individualism to be an individual level. This study examine the moderating effect of collectivism/individualism as a dimension of culture on the relationship between attitude and named factors including: Trust (integrity, benevolence, and ability), perceived risk, attribute of innovation (relative advantage, compatibility, and complexity), and subjective norm. This study also examine the mediating effect of attitude between including factors and intention toward online shopping. Results revealed that significant moderation effects on the relationship between attitude and subjective norm, compatibility and relative advantage. Moreover, the support was found for partial mediation of attitude on the relationship between some factors including: trust, subjective norm, relative advantage, compatibility and intention. However, the attitude couldn‟t be mediated for complexity and perceived risk with intention. The result of structural equation modeling indicated that the level of online shopping intention was relatively high and direction of attitude toward online shopping was positive among students. In addition, the study showed that trust, perceived risk, subjective norm, attribute of innovation (relative advantage,compatibility) were significantly and positively correlated with the attitude toward online shopping. Furthermore, the result showed attitude and subjective norm were significantly and positively correlated with online shopping intention. The recommendations which can be derived from the findings of the study are offered and divided into three parts, namely, for the online retailers, Telekom Malaysia as the main telecommunication and Internet service provider in the country and the Government of Malaysia. Based on the findings of the study, it is therefore recommended that online retailers are required to consider the online shopping in order to increase their chances of success in retailing business via the Internet.